Enhancing Arabic Language Learning: Insights from Implementing 'Ta'alam al-'Arabiyyah Ma'ana' Volume 1 - Rakhmaniah, Nur Azizahtur; Anwar , Najih (Universitas Muhammadiyah Sidoarjo, 2024)
This study delves into the implementation of the instructional book 'Ta'alam al-'Arabiyyah Ma'ana' Volume 1 in Arabic language courses at Madrasatul Alsun Sidoarjo. Employing a descriptive qualitative approach, data was gathered through observation, interviews, and documentation. The analysis encompassed data collection, reduction, and conclusion drawing. The findings reveal a structured three-stage learning process, encompassing lesson planning, implementation, and evaluation. Supportive factors include proficient educators, student focus, discipline, and adequate facilities. Conversely, challenges encompass student attentiveness, suboptimal learning environments, and fluctuating motivation. Mitigative strategies involve targeted verbal cues, crowd control measures, and sustained motivation through reinforcing the significance and goals of Arabic language acquisition. This research provides valuable insights for optimizing Arabic language education. Highlight: Three-Stage Learning Process: The study outlines a structured approach to Arabic language education, encompassing lesson planning, implementation, and evaluation, demonstrating the importance of a well-organized curriculum. Factors Influencing Success: Proficient educators, student focus, discipline, and adequate facilities are identified as supportive elements, emphasizing the role of these factors in effective language instruction. Overcoming Challenges: The research highlights strategies to address challenges like student attentiveness, suboptimal learning environments, and fluctuating motivation, underscoring the need for proactive measures to enhance the learning experience. Keyword: Arabic Language Education, Instructional Book, Implementation, Qualitative Research, Learning Process